Em busca da eficiência na execução dos serviços públicos de limpeza urbana e manejo de resíduos sólidos - Sousa, Augusto Corrêa de (2021)
The present work seeks to analyze the efficiency in the provision of the public service of urban cleaning and solid waste management made by Companhia de Urbanização de Goiânia. (COMURG) Initially, an approach will be made on the origin, terminology and effectiveness of fundamental rights, as well as the connection with the idea of the existential minimum and the obstacles imposed by the theory of the reservation of the possible, without neglecting the mention of the rights to health, to the ecologically balanced environment and basic sanitation. The costs of rights will also be analyzed in opposition to the principle of prohibition of social setbacks. Then, an overview will be made about the competence to provide urban cleaning services and solid waste management, public policies and legal-institutional arrangement, concept and forms of providing public services and forms of funding. The basic concepts of the Economic Analysis of Law will be worked out and, at the end, a comparative analysis of the indicators and information of the National Sanitation Information System (SNIS) for the cities of Goiânia, Belém, Campinas (SP), Curitiba, Guarulhos will be carried out. (SP), Maceió, Porto Alegre, Recife, São Gonçalo (RJ) and São Luís. In the final part of the work, the balance sheets of the COMURG published in the last twenty-five years will also be analyzed. Finally, Altman's Z'-Score and Z ’’ - Score tests will be applied to COMURG’s 2019 balance sheet to gauge the state’s solvency.